Performance comparison of Flutter platform GUI in web and native environments - Piskor, Juliusz; Badurowicz, Marcin (Journal of Computer Sciences Institute, 2023)
This article compares the performance of the Flutter framework’s graphical user interface (GUI) in a Windows platform native environment and in a web environment on the same device. The purpose of the article is to make a comparative analysis of screen building and rebuilding times in both environments. For the purpose of the paper, a test application has been created in which screens of different types of complexity are included. The stated theses: "The Flutter platform is less efficient in the web environment compared to the native environment in terms of view loading times." and "The Flutter platform is less efficient in a web environment compared to a native environment in terms of view rebuilding time" have been proven.